Высокочувствительная установка для оценки изменения показателя преломления водных растворов - Podkamen, L. I.; Gavrylyak, M. S. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
The automated high-sensitivity setup for estimation of change of water solutions refraction index with accurate within 10–7 is developed. The methodical recommendations on its use are listed, the efficiency and appropriateness of the setup are shown.